Analisis Tindak Pidana Pencemaran Nama Baik Oleh Aktivis Lingkungan Hidup Terhadap Tambak Udang Ilegal di Taman Nasional Karimunjawa (Study Kasus Daniel Frits Tangkilisan) - Nur Azmi, Fitri; Nurhilmiyah, Nurhilmiyah (UNES Law Review, 2024)
This research aims to analyze criminal acts of defamation by environmental activists against illegal shrimp ponds in Karimunjawa National Park. The research approach uses a statutory approach, namely using the laws of the Unitary State of the Republic of Indonesia, the Criminal Code. Criminal Procedure Code, Law Number 1 of 2024 concerning Information and Electronic Transactions and Article 66 of Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH). Type of research, in this research the author uses qualitative data. The results of this research are that a speech can be said to be hate speech if there is a malicious intention from the perpetrator of the speech to encourage hostility, invite discrimination, and calls for violence (incitement to violence), against certain groups of the population based on ethnicity, religion, race and between groups and Daniel Frits' upload is far from all of that. Efforts that an activist can take if he is criminally sued is by filing an appeal against the judge's verdict, in this case Daniel, who has been sentenced by the judge, files an appeal with the help of his attorney, because Daniel's attorney assesses Daniel as an environmental fighter in Karimunjawa who has experienced the impact. due to illegal shrimp farming, and is supported by Articles 65 and 66 of Law Number 32 of 2009 concerning Environmental Protection and Management. Legal Protection of Environmental Activists in a Criminal Perspective, From a criminal law perspective environmental activists are supported by Article 66 of Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) which states that everyone who fights for the right to a good and healthy environment cannot be prosecuted criminally or sued civilly, it has multiple interpretations and is not implemented